Parallel computing technologies 11th International Conference, PaCT 2011, Kazan, Russia, September 19-23, 2011. Proceedings - Malyshkin, Victor (Lecture Notes in Computer Science, 2011)
This book constitutes the proceedings of the 11th International Conference on Parallel Computing Technologies, PaCT 2011, held in Kazan, Russia on September 19-23, 2011. The 44 full papers presented together with 2 invited papers were carefully reviewed and selected from 68 submissions. The papers are organized in topical sections on models and languages, cellular automata, parallel programming tools and support, and applications.